Malaysian ESL students' attitude, perceptions and preferences of teacher written feedback in writing / Suzie Rahman Wong - Wong, Suzie Rahman (Universiti Teknologi MARA, Sabah, 2021)
Students' perception and preferences on teacher-written feedback (TWF) tend to vary in different learning contexts. This study explores the perceptions and preferences of TWF among 78 Malaysian ESL students in a public pre-university college in Malaysia. Quantitative data were obtained from a questionnaire to examine the students' general attitude and perceptions of TWF, and their preferences of the types and amount of written feedback received on their written work. This study reveals that the ESL students had a positive attitude and perception of the teacher-written feedback practice based on the perceived usefulness of the feedback, and the integrative-feedback type that combines both the content and language feedback was mostly favoured. The result also shows that the students had a high preference for indirect coded corrective feedback strategy in highlighting language errors, and preferred a large amount of feedback that highlighted all errors on their written work. These findings potentially help teachers to make a more informed decision when using teacher-written feedback so as to cater to students' varying needs and perceptions in order to improve its use in writing.